Smart Energy Systems – District heating, industrial sector and marine transportation transformation - Østergaard, Poul Alberg; Cabrera, Pedro; Johannsen, Rasmus Magni (International Journal of Sustainable Energy Planning and Management, 2026)
This 49th volume of the International Journal of Sustainable Energy Planning and Management presents articles from the 11th Smart Energy Systems Conference held in Copenhagen, Denmark in 2025. The conference invites academia, industry, consultancy, and utilities to engage and discuss the transition of the energy system. District heating has always been a strong focus point of the conference, as is also evident in the present 49th volume of the IJSEPM. Topics presented in this volume include a study on alternative heat sources for heat pumps in district heating, such as wastewater and river water. District heating continues to be a focal point, in a study exploring hybrid network solutions for further development of district heating systems, and in a study on decarbonisation of combined district heating and cooling systems. Also connected to district heating, this volume presents work on novel methods for estimations of heat demand and heat sources for district heating across the European Union, in addition to a study on the mapping of waste heat potentials, and lastly, the global warming potential of district heating in Finland. Finally, this volume presents work on industry transformations and prominent barriers to this transformation, and a rare study on the maritime sector and the modelling of sustainable fuel pathways.